Pelimpahan Utang Terhadap Ahli Waris Prerspektif Hukum Islam dan Hukum Perdata - Isnainy Nurul Ammah; Ika Setyorini SH.,MH. (Hukum Keluarga Islam, 2023)
balanced with the differences in the responsibilities of each heir to his family. Even so, the responsibility of the heir to the inheritance of the inheritance does not always leave the inheritance alone, but sometimes the heir has to pay the debt of the inheritance, both the debt to Allah SWT and the debt to fellow human beings. The theme of this research is Delegation of Debt to Heirs from the Perspective of Islamic Law and Civil Law. Therefore, this research reveals the formulation of the problem which is then written in the formulation of the research problem, including: (1) How is the settlement of the “Pelimpahan Utang Terhadap Ahli Waris Perspektif Hukum Islam dan Hukum Perdata (Studi Kasus di Dukuh Nganggrek Desa Cabak Kecamatan Tlogowungu Kabupaten Pati) (2) How is Delegation of Debt to Heirs in the Perspective of Islamic Law? (3) How is the Delegation of Heir Debt in the Perspective of the Civil Code? To answer these problems, the authors conducted research using literature studies or types of library research (library research). Library research (library research) to answer the first and second problem formulations, then using field research (field research), to answer the third problem formulation. With data collection techniques using interviews and interviews as well as data analysis techniques using analytical descriptive methods. The results of the study can be concluded that the position of the heir has been clearly defined in the Qur'an, but this is not the case with the discovery of inheritance according to Islamic law, because even among the scholars there are still differences of opinion regarding what is included in the inheritance. legacy.According to Islamic law, the responsibility of the heir to the heir's debt is limited to the amount of his inheritance, and cannot cause harm to the heir himself. Meanwhile, according to civil law, if the heir refuses to be given an inheritance, the heir is not burdened with the responsibility of the heir after the death of the heir. However, Islamic law and civil law suggest resolving the problem by resolving it in a non-litigation way (deliberation) or alternative dispute resolution in the form of out-of-court dispute resolution in other words resolved in an amicable way.